1984
DOI: 10.1115/1.3246745
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Description of Hydrodynamic Fragmentation Processes Within Thermal Detonation Waves

Abstract: Large-scale vapor explosions are described by thermal detonation waves, proceeding through a fuel-coolant mixture. A two-phase flow model is used for modeling the processes inside a wave. One phase is formed by the drops of melt and the other by the coolant and the fragments. For the interfacial transfer relations between the phases new descriptions are presented, which extend earlier thermal detonation models. The fragmentation behavior can be calculated from two different models, one based on deformation bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This mechanism of instabilities developing and being stripped at the equator is similar in concept to the model proposed in [13] in which wave rings around the axis of the droplet in the flow direction, are stripped as they travel towards the equator of the drop. The main difference between the model and the experimental observations is the type of instability that is dominant.…”
Section: Hydrodynamic Instabilitiessupporting
confidence: 65%
See 1 more Smart Citation
“…This mechanism of instabilities developing and being stripped at the equator is similar in concept to the model proposed in [13] in which wave rings around the axis of the droplet in the flow direction, are stripped as they travel towards the equator of the drop. The main difference between the model and the experimental observations is the type of instability that is dominant.…”
Section: Hydrodynamic Instabilitiessupporting
confidence: 65%
“…In a propagating meltcoolant interaction, the fine fragmentation of the melt governs the rapid increase of interfluid surface area and heat transfer. Previous studies of propagating vapour explosions [12,13] have shown that the fragmentation mechanisms of single melt drops can be classified into two main groups: thermally-induced mechanisms, driven by vapour film collapse and subsequent bubble dynamics, or hydrodynamic fragmentation mechanisms due to the relative velocity between the melt and coolant. Although much is known about each class of fragmentation mechanism, the transition from thermal to hydrodynamic fragmentation as the ambient flow velocity is increased, which is relevant to the developing phase of a steam explosion, is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A number of phenomenological models have been proposed to depict the fine fragmentation of the high temperature liquid [1], which are commonly categorized into two groups: thermal [2,3] and hydrodynamic [4,5]. The thermal fragmentation models are based on the formation of micro coolant jets that penetrate the surface of the hot melt or the generation of local high-pressure regions which stretch and break up the melt.…”
Section: Introductionmentioning
confidence: 99%
“…DS-15 and 18 of Kim's experiment (Kim, 1985) on gallium droplets, prediction model based on gas-liquid system (Pilch and Erdman, 1987), capillary wave model and Taylor wave model (Burger, 1984) are introduced to validate the calculations of Eq. (27).…”
Section: Discussionmentioning
confidence: 99%
“…Ranger and Nicholls (1969) built a boundary layer stripping model based on droplet-stripping process in aerodynamic experiments. Burger (1984) gave an introduction to Rayleigh-Taylor instability model and capillary wave stripping model.…”
Section: Introductionmentioning
confidence: 99%